Second trimester abortion service at a provincial public hospital - Pandit, Ram Naresh; Thakur, Murari (Nepal Journal of Obstetrics and Gynaecology, 2020)
Aims: To determine the demographic and clinical profile of clients receiving second trimester abortion service at a provincial hospital. Methods: This is a retrospective study of second trimester abortion service provided at Provincial Public Hospital Janakpurdham at southern part of Nepal from 2014 to 2017. Data were collected from hospital record and analysis performed using MS Excel. Result: There were 144 cases who received second trimester abortion service in four years. Annual clients’ number linearly increased from 16 to 54. Nearby people were the maximum clients. Majority (85%) were multiparous and of early second trimester (12-15 weeks, 71%). Common indication recorded was mental health (83%) but lacks verification. Intervention method was combined (56%) and contraception of choice was DMPA (44%). Conclusion: Demand of second trimester service is increasing every year. Indication of abortion needs to be scientifically verifiable. Injectable hormonal contraception is preferred by clients. Keywords: abortion, client profile, second trimester